2018
DOI: 10.1148/radiol.2017171161
|View full text |Cite
|
Sign up to set email alerts
|

Observed Deposition of Gadolinium in Bone Using a New Noninvasive in Vivo Biomedical Device: Results of a Small Pilot Feasibility Study

Abstract: Purpose To perform a preliminary evaluation of a noninvasive measurement system to assess gadolinium deposition in bone and to investigate the relationship between the administration of gadolinium-based contrast agents (GBCAs) and gadolinium retention in bone. Materials and Methods In vivo measurement of gadolinium retention in tibia bones was performed in 11 exposed subjects who previously received GBCAs (six exposed subjects were from a study performed 5 years previously involving injection of GBCAs in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 34 publications
4
59
0
1
Order By: Relevance
“…While the detection limits of EDS are typically around 0.5 wt%, SR-XRF spectrometry (as www.nature.com/scientificreports www.nature.com/scientificreports/ employed in the present study) features a much higher sensitivity down to sub-ppm 24 , thus making this method more suitable for the local analysis of trace elements like Gd. Indeed, the anticipated Gd concentrations in bone after exposure to GBCA are within few ppm, which is supported by the bulk measurements (up to 1.77 µg Gd/g bone 37 ) and in vivo experiments (mean 1.19 µg Gd/g bone 19 ).…”
Section: Analysis Ex Vivo Localization Within Bonesupporting
confidence: 68%
See 1 more Smart Citation
“…While the detection limits of EDS are typically around 0.5 wt%, SR-XRF spectrometry (as www.nature.com/scientificreports www.nature.com/scientificreports/ employed in the present study) features a much higher sensitivity down to sub-ppm 24 , thus making this method more suitable for the local analysis of trace elements like Gd. Indeed, the anticipated Gd concentrations in bone after exposure to GBCA are within few ppm, which is supported by the bulk measurements (up to 1.77 µg Gd/g bone 37 ) and in vivo experiments (mean 1.19 µg Gd/g bone 19 ).…”
Section: Analysis Ex Vivo Localization Within Bonesupporting
confidence: 68%
“…Series of in vivo experiments by M. Lord et al contributed substantially to the current knowledge about Gd retention. The group developed an in vivo XRF device and obtained quantitative data on Gd content in the bone tissue of exposed patients in comparison with control subjects 18,19 .…”
mentioning
confidence: 99%
“…Gadolinium deposition occurs in tissues other than the brain, most particularly bone, which has been postulated to serve as a reservoir for Gd that may subsequently deposit in other tissues . Although clearance by multiple organs is rapid following GBCA administration, that by the brain and bone are reported to be slower .…”
Section: Discussionmentioning
confidence: 99%
“…Gadolinium deposition occurs in tissues other than the brain, most particularly bone, which has been postulated to serve as a reservoir for Gd that may subsequently deposit in other tissues. 33,[52][53][54] Although clearance by multiple organs is rapid following GBCA administration, that by the brain and bone are reported to be slower. 54 In the current study, Gd content in the bone was approximately 21 times the brain levels for LPS-treated rats and approximately 60 times that of control rats at 6 weeks following GBCA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in gadolinium levels in bone and urine have been observed between individuals experiencing symptoms and those who are not [41]. A large study with a control population found more new symptoms within 24 hours after exposure to GBCA than after unenhanced MRI.…”
Section: Self-reported Clinical Symptomsmentioning
confidence: 99%